Defence Efficacy in Practice and Competition. A Case Study in Women's Volleyball - Maria Inmaculada Giménez-Ibarra; José M. Palao (Wydawnictwo Naukowe Uniwersytetu Szczecińskiego, 2015)
The aim of this study was to compare the player positions, situations, techniques, and efficacy in defence between practice and competition for a women’s professional volleyball team. The sample was a Spanish professional women’s volleyball team. The defence actions carried out in three sessions of the competitive season and two in-season matches were studied (794 rallies in practice and 166 rallies in competition). The variables studied were: actions done, defence zone, player role, type of attack, court defence technique, game phase, situations, level of execution of the defence team system, block efficacy, defence efficacy, and result of the rally for the analysed team. Descriptive and inferential analyses of the data were done (Mann-Whitney U, and Chi-Square Test and likelihood ratio). Differences in defence systems and efficacies were found between practice and competition. A higher collective efficacy was found in competition, and higher levels of individual block and defence efficacies were found in practice. The results show the need to reconsider the way match analysis is done. Consideration should not only be given to the actions done with the ball when analysing players’ performance.